2020
DOI: 10.48084/etasr.3590
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study on the Way Bottom Widening of Pier Foundations Affects Seismic Resistance

Abstract: The resistance of a pier to horizontal loads, like seismic loads, is due to the flexural rigidity of its foundations and the horizontal subgrade reaction. In the event of a massive earthquake, the latter becomes very small because of the softening of the ground, while the structure may experience a large inertial force and lateral spreading pressure. Therefore, structures with high seismic resistance are required in areas with high seismicity. When a wide caisson is used as a pier foundation, a rotational resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Therefore, the FW should be extremely wide when the seismic load is large. However, the results of the horizontal loading test of pier models where the FW was changed revealed that the seismic resistance becomes extremely high by widening the FW because the vertical SR becomes large [6]. It has been also highlighted that the FW dependence of the vertical SRM is lower than that of the horizontal SRM [7].…”
Section: Imentioning
confidence: 99%
“…Therefore, the FW should be extremely wide when the seismic load is large. However, the results of the horizontal loading test of pier models where the FW was changed revealed that the seismic resistance becomes extremely high by widening the FW because the vertical SR becomes large [6]. It has been also highlighted that the FW dependence of the vertical SRM is lower than that of the horizontal SRM [7].…”
Section: Imentioning
confidence: 99%
“…Therefore, if the seismic load is very large, FW should be very wide. Conversely, an experimental study on the seismic resistance of piers with various FWs has shown that the piers with wider FWs are extremely seismic resistant due to the increase in vertical subgrade reaction [9]. The results have shown that the calculation equation of the design practice could underestimate SRM for wide FW conditions.…”
Section: Introductionmentioning
confidence: 97%
“…All ground motions were imposed on the NPP models in horizontal direction. Normally, the lateral acceleration or displacement responses of structures are monitored during earthquakes [20][21][22]. The seismic response of both non-and base-isolated NPP structures was obtained in terms of the FRS.…”
Section: Numerical Modelingmentioning
confidence: 99%